Prophylactic and therapeutic potential of magnolol-loaded PLGA-PEG nanoparticles in a chronic murine model of allergic asthma - Wang, Junyi; Xian, Mo; Cao, Hui; Wu, Lei; Zhou, Libo; Ma, Yihe; Fan, Long; Lin, Lin; Li, Guoping; Huang, Qinmiao; Huang, Shau-Ku; Xiao, Xiaojun (Frontiers in Bioengineering and Biotechnology, 2023)
Magnolol is a chemically defined and active polyphenol extracted from magnolia plants possessing anti-allergic activity, but its low solubility and rapid metabolism dramatically hinder its clinical application. To improve the therapeutic effects, magnolol-encapsulated polymeric poly (DL-lactide-co-glycolide)-poly (ethylene glycol) (PLGA-PEG) nanoparticles were constructed and characterized. The prophylactic and therapeutic efficacy in a chronic murine model of OVA-induced asthma and the mechanisms were investigated. The results showed that administration of magnolol-loaded PLGA-PEG nanoparticles significantly reduced airway hyperresponsiveness, lung tissue eosinophil infiltration, and levels of IL-4, IL-13, TGF-β1, IL-17A, allergen-specific IgE and IgG1 in OVA-exposed mice compared to their empty nanoparticles treated mouse counterparts. Magnolol-loaded PLGA-PEG nanoparticles also significantly prevented mouse chronic allergic airway mucus overproduction and collagen deposition. Moreover, magnolol-encapsulated PLGA-PEG nanoparticles showed better therapeutic effects on suppressing allergen-induced airway hyperactivity, airway eosinophilic inflammation, airway collagen deposition, and airway mucus hypersecretion, as compared with magnolol-encapsulated poly (lactic-co-glycolic acid) (PLGA)nanoparticles or magnolol alone. These data demonstrate that the protective effect of magnolol-loaded PLGA-PEG nanoparticles against the development of allergic phenotypes implicating its potential usefulness for the asthma treatment.